A synthesis of the main conditions for effectiveness of small-scale fisheries co-management - Serafini, Thiago Zagonel (Sustainability in Debate, 2018)
Despite the emergence of small-scale fisheries co-management initiatives or at least the fact that it is recommended as an alternative to conventional management approaches, its effectiveness is highly dependent on the social, political, economic and ecological context. Identifying which conditions could to further this process is one of the research priorities themes of the adaptive co-management approach, with implications both to the process analysis and to subsidize current practical experiences. Considering that co-management arrangements have been created in different small-scale fisheries contexts in Brazil, in this review the main conditions for its effectiveness were summarized from the specialized literature. It was concluded that an "ideal scenario" for the small-scale fisheries co-management reinforces small-scale process and lack of socioecological complexity, in detriment of the high complexity of many coastal socioecological systems in which small-scale fisheries take part.